p53-mediated control of aspartate-asparagine homeostasis dictates LKB1 activity and modulates cell survival - Longfei Deng (Nature Portfolio, 2020)
Cancer cells can produce asparagine, yet both the regulation and biological functions of asparagine are unclear. Here the authors show that p53 suppresses asparagine synthesis and disrupts asparagine-aspartate homeostasis contributing to tumor growth inhibition, and that asparagine and aspartate modulates AMPK-mediated p53 activation by physically binding to and regulating LKB1.